Meta-Analysis: Factors Related with Premarital Sexual Behavior in Adolescents - Aktif Cahyaning Tyas; Hallisa'tu Zahro; Putri Fortuna Salsabila; Aem Ismail; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Premarital sexual behavior is a sexual activity carried out before marriage. Premarital sexual behavior is a health priority in adolescents because it causes unwanted pregnancies, abortions, STIs, HIV/AIDS and even death. Parents, peers, community environment, economic and cultural conditions influence premarital sexual behavior. This study aims to analyze the effect of peers, smoking behavior, alcohol consumption, exposure to pornography and rural areas on premarital sexual behavior in adolescents. Subjects and Method: This was a systematic review and meta-analysis of study articles. Data obtained from databases including Google Schoolar, Pubmed and Science Direct. Article search was carried out by considering eligibility criteria with the PICO model. Population: adolescents. Intervention: high peer pressure, smoking behavior, alcohol consumption, exposure to pornography, and rural areas. Comparation: low peer pressure, non-smoking, no alcohol consumption, no exposure to pornography, and urban areas. Outcome: premarital sexual behavior. The articles were collected with keywords including